Model Pembelajaran Student Facilitator and Explaining dalam Meningkatkan Motivasi dan Hasil Belajar Al-Qur’an Hadits Siswa Madrasah Ibtidaiyah - agri bastiar; Raehang R; Pairin P (Diniyah: Jurnal Pendidikan Dasar, 2020)
This study aims to increase motivation and learning outcomes of students in the Qur'an Hadith at MIN 1 Kendari through the implementation of the Student Facilitator And Explaining learning model. This is a classroom action research. The research subjects were students of class V B MIN 1 Kendari with 27 students. The research procedure includes planning, implementation, observation, evaluation and reflection. Data collection techniques used observations, tests, questionnaires, and documentation which were analyzed descriptively qualitatively. The results showed that the use of the Student Facilitator and Explaining learning model could increase the learning motivation of students at MIN 1 Kendari with the presentation of student learning motivation reaching 88.88% with very high category. There was also an increase in student learning outcomes after the implementation of the Student Facilitator And Explaining learning model with a good percentage of student learning outcomes of 81.48%.Keywords: Student Facilitator And Explaining (SFAE), Learning Motivation, Learning Outcomes of Al-Qur'an Hadith